2015
DOI: 10.1063/1.4914062
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure barrier discharge at high temperature: Diagnostics and carbon nanotubes deposition

Abstract: Atmospheric pressure dielectric barrier discharge (DBD) in Ar/H2 gas feed with C2H2 or CH4 admixture was studied at room and high temperature of 680 °C by plasma diagnostics (electrical measurements, fast camera imaging, and optical emission spectroscopy). It was shown that filamentary DBD in pure Ar or Ar/H2 can be converted into homogeneous discharge by an acetylene admixture. Fast intensified charge-coupled device (ICCD) camera proved that this homogeneous discharge is an atmospheric pressure glow discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…S1 (see Supporting Information). Recently, it was shown that DBD in Ar/C 2 H 2 mixture can be ignited in the homogeneous mode, so called atmospheric pressure glow discharge (APGD) [42]. The appearance of several current peaks was attributed to the fact that the discharge did not burn in the whole discharge gap at the same time.…”
Section: Electrical Characterization and Oesmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 (see Supporting Information). Recently, it was shown that DBD in Ar/C 2 H 2 mixture can be ignited in the homogeneous mode, so called atmospheric pressure glow discharge (APGD) [42]. The appearance of several current peaks was attributed to the fact that the discharge did not burn in the whole discharge gap at the same time.…”
Section: Electrical Characterization and Oesmentioning
confidence: 99%
“…Therefore, it is advantageous to find a monomer which whose admixture will lead to the ignition of DBD in a homogeneous mode. Recently, Eliáš et al demonstrated that the so called atmospheric pressure glow discharge (APGD) can be ignited in the mixture of Ar and C 2 H 2 [42].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma polymerization is known to be a suitable method for the deposition of many biomaterial coatings [8,9]. Plasma polymerization is in the class of plasma-enhanced chemical vapor deposition (PECVD) methods, which are successfully used for example for thin film deposition [10], surface modification [11,12], or growing of nanomaterials [13][14][15]. Plasma deposition of 2-methyl-2-oxazoline and 2-ethyl-2-oxazoline has already been performed in low-pressure radio frequency (RF) discharge [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…During the cleaning process, the high energy plasma level disrupted the structure of organic substances contaminating the material and removed impurities from the surface [130]. Plasma is also used in the industrial production of nanomaterials [131,132] and synthesis and application of thin coatings [133][134][135].…”
Section: Plasmamentioning
confidence: 99%